Pengembangan Virtual Laboratory Sistem Ekskresi dalam Meningkatkan Motivasi Belajar Siswa SMA - Widi Cahya Adi; Suratno Suratno; Mochammad Iqbal (Pascasarjana Universitas Negeri Malang (UM), 2016)
Abstract: The purpose of research is to develop a Virtual Laboratory excretory system and determine the effect in improving students' motivation in class XI SMAN 2 Bondowoso. The development study refers to the development model Reflective, Recursive, Design, and Development (R2D2), afterward the product test performed by a quasi-experimental methods. The data collection was conducted by interview, validation expert, and ARCS questionnaires. The product validation result by material experts, development expert of teaching materials, flash media experts, and practitioners shows the percentage 93.05%, 90.62%, 94.16%, 93.88% (